Hyperbilirubinemia as a predictor of severity of acute appendicitis. Issue 8 (August 2019) - Akai, Masaaki; Iwakawa, Kazuhide; Yasui, Yuichi; Yoshida, Yusuke; Kato, Takuya; Kitada, Koji; Hamano, Ryosuke; Tokunaga, Naoyuki; Miyaso, Hideaki; Tsunemitsu, Yosuke; Otsuka, Shinya; Inagaki, Masaru; et al.
Objective: This study aimed to investigate the clinical significance of preoperative hyperbilirubinemia in Japanese patients and to assess its clinical potential as a predictor of the severity of acute appendicitis. Methods: We studied 318 patients with appendicitis who underwent appendectomy between July 2010 and June 2017. We analyzed preoperative data including age, sex, white blood cell count, C-reactive protein (CRP) level, fever, peritoneal irritation signs, and serum total bilirubin level as potential risk factors for complicated (perforated or gangrenous) appendicitis, using multivariate analysis. Results: Complicated appendicitis was significantly more frequent in patients with hyperbilirubinemia (>1.1 mg/dL), high CRP level (>0.5 mg/dL), positive peritoneal irritation signs, and fever (>37.3°C). Multivariate analysis revealed older age (>64 years), hyperbilirubinemia, high CRP level, and fever (odds ratios 3.36, 1.75, 7.61, and 2.43, respectively) as risk factors for complicated appendicitis. Multivariate analysis also identified hyperbilirubinemia, high CRP level, and fever (odds ratios 1.99, 5.90, and 2.72, respectively) as risk factors for complicated appendicitis among patients aged <65 years. Conclusions: Hyperbilirubinemia, high CRP level, and fever may be useful predictors of the severity of acute appendicitis, with hyperbilirubinemia being especially useful among patients aged <65 years.